Consumo máximo de oxigênio e variabilidade da frequência cardíaca de homens saudáveis e diabéticos tipo I em região de fronteira - Santos, Hemerson Dinis Oliveira (2019)
Introduction: Hyperglycemic states have been indicated as triggers of chronic complications in DM1, due to cellular structural alterations, triggered by chronic hyperglycemia. This fact contributes to the fact that the physiological responses of adaptations to physical exercise are deficient and, therefore, the individual with DM1 presents a change in the cardiorespiratory regulation capacities. Objectives: To compare the maximum oxygen consumption and heart rate variability of healthy men and type I diabetics. Methods: This was a descriptive, cross-sectional observational study composed of 30 male volunteers, divided into two groups: GC (n = 15) (27.1 ± 7.6 years) and DM1 (n = 15) (27.5 ± 8.7 years). Vital and post-exercise stress (HR, SBP, DBP and SatO2) rest periods, glycemic control (capillary glycemia - pre and post exercise test, glycated hemoglobin - Hb1Ac and mean glycemia), body composition (Inbody, model 120), Heart Rate Variability - Resting HRV (POLAR® digital cardiofrequency meter), maximum oxygen consumption test on cycle ergometer (CEFISE - Biotec 9100 model) and Physical Activity Level - NAF (IPAQ long version). Descriptive statistics were calculated with means and standard deviation and normality analysis of all data using the Kolmogorov-Smirnov test. With the normal data, the unpaired t test was used to compare the DM1 and CG groups. For all statistical analyzes, the Instat - Sigma software was used. The significance value for data analysis was 5%. Results: The evaluations showed statistical differences for the variables of pre and post-exercise stress GCAP, Hb1Ac, mean blood glucose, HRV, peak VO2 and time of effort test, favoring the control group. Conclusion: Due study suggests that patients with DM1 present low cardiorespiratory capacity and low HRV, predominantly the autonomic components of physiological modulation of the sympathetic nervous system, which may be correlated with the low level of physical activity of the samples and the glycemic profile presented.